Pengaruh Harga Kelengkapan Produk Dan Lokasi Terhadap Kepuasan Konsumen Di 212 Mart - Nadia Ika Purnama; Mhd. Fauzan Habibi Nasution; Rini Astuti (CERED Indonesia Institute, 2022)
This study aims to find out the influence of price, completeness of products, and location on customer satisfaction in 212 marts, to know the influence of prices on consumer satisfaction in 212 marts, to know the effect of product completeness on customer satisfaction in 212 marts, and to know the influence of location on customer satisfaction in 212 marts. The population in the study was all customers who shopped at 212 marts as many as 96 respondents. Data is collected through the dissemination of questions to respondents. The approach of this study is associative with multiple linear regression analysis tools, testing is conducted with classical assumption tests and hypotheses. The results of the discussion are known to have a significant and positive relationship of prices to consumer satisfaction in 212 marts. Product completeness has a significant and positive effect on customer satisfaction at 212 marts. Location has a significant and positive effect on customer satisfaction at 212 marts.